A new species of Neotraginops Prado (Diptera: Odiniidae) from Mexico and Belize, with additional records for Odinia coronata Sabrosky in Mesoamerica - Hernández-Ortiz, Vicente; Dzul-Cauich, José F. (Zootaxa, 2014)
Neotraginops mexicanus n. sp. is described and illustrated based on specimens from Mexico and Belize, representing the second known species for the genus. Additional records for Odinia coronata Sabrosky from Mexico and Nicaragua are provided.